Interactions of human serum albumin with phosphate and Tris buffers: impact on paclitaxel binding and nanoparticles self-assembly (2024)
ABSTRACT: Aim: To investigate the conformational changes in human serum albumin (HSA) caused by chemical (CD) and thermal denaturation (TD) at pH 7.4 and 9.9, crucial for designing controlled drug delivery systems with paclitaxel (PTX). Methods: Experimental and computational methods, including differential scanning calorimetry (DSC), UV-Vis and intrinsic fluorescence spectroscopy, mean diameter, polydispersity index (PDI), ζ-potential, encapsulation efficiency (EE), in vitro release and protein docking studies were conducted to study the HSA denaturation and nanoparticles (NPs) preparation. Results: TD at pH 7.4 produced smaller NPs (287.1±12.9nm) than CD at pH 7.4 with NPs (584.2±47.7nm). TD at pH 9.9 exhibited high EE (97.3±0.2%w/w) with rapid PTX release (50% within 1h), whereas at pH 7.4 (96.4±2.1%w/w), release only 40%. ζ-potentials were around −30mV. Conclusion: Buffer type and pH significantly influence NP properties. TD in PBS at pH 7.4, provided optimal conditions for a stable and efficient drug delivery system.